On the impact of spatial heterogeneity and drift rate in a three-patch two-species Lotka–Volterra competition model over a stream - Chen, Shanshan; Liu, Jie; Wu, Yixiang (Zeitschrift für angewandte Mathematik und Physik, 2023)
In this paper, we study a three-patch two-species Lotka–Volterra competition patch model over a stream network. The individuals are subject to both random and directed movements, and the two species are assumed to be identical except for the movement rates. The environment is heterogeneous, and the carrying capacity is lager in upstream locations. We treat one species as a resident species and investigate whether the other species can invade or not. Our results show that the spatial heterogeneity of environment and the magnitude of the drift rates have a large impact on the competition outcomes of the stream species.